THE CONCEPT OF TAUHID EDUCATION VALUE (AQIDAH) IN NATIONAL EDUCATION SYSTEM PERSPECTIVE - Nurhadi, Nurhadi; Lubis, Zainul Bahri (AL-ISHLAH: Jurnal Pendidikan, 2019)
This study aims to determine the values of Tauhid Education in the National Education System and the relevance of the National Education System Law No. 20 of 2003 in strengthening the values of Tauhid Education. This research method uses a type of library research or literature study (library research). Using two data sources, namely: 1). The primary data is law No. 20 of 2003 concerning the National Education System. 2). Secondary data is literature related to this research. The results of the study were obtained: 1) the values of Tauhid education contained in Chapter II Article 3 read: "National Education aims to develop the potential of students to become human beings who believe and fear God the Almighty". Chapter V Article 12 paragraph 1 point A reads: "Every student in each education unit has the right: get religious education in accordance with the religion he adheres to and is taught by educators who are of the same religion". Chapter X Article 36 paragraph 3 point A reads: "The curriculum is prepared in accordance with the level of education within the framework of the Unitary State of the Republic of Indonesia by taking into account: Increased faith and piety". 2) Relevance of the Law on National Education System No. 20 of 2003 in strengthening the values of Tauhid education that the main purpose is: "Faithful and devoted to the Almighty God". Then the right of the first student is to get religious education in accordance with a religion that is followed and taught by religious educators. And the curriculum is arranged in accordance with the level of education within the framework of the Unitary State of the Republic of Indonesia with the first increase, namely faith and piety.